Penyuluhan Pemeriksaan Kesehatan Diabetes Pada Ibu-Ibu Di Desa Sidomulyo Kecamatan Medang Deras Kabupaten Batu Bara Sebagai Langkah Awal Pencegahan Dan Pengobatan - Rizqy Fadhila Putri; M. Al-Ghifari Syah; Ade Ulfa Damaiyanti Rambe; Tsania Zikri Eryana Sitepu; Ananda Syahrani Sihombing (Jurnal Nirta : Inovasi Multidisiplin, 2025)
Diabetes Mellitus is a global health problem that poses a serious threat, including in rural areas. This study aims to identify the health status and diabetes risk in mothers in Sidomulyo Village, Medang Deras District, Batu Bara Regency, as an initial step in prevention and treatment. Using a descriptive-qualitative method, this study involved 50 mothers aged 30-60 years who were selected thru purposive sampling. Data was collected thru a structured questionnaire about lifestyle and family history, as well as a random blood sugar (RBS) test using a glucometer. The research results show that 32% of respondents are in the pre-diabetes category and 12% are indicated to have undiagnosed diabetes. This finding is supported by qualitative data indicating unhealthy lifestyles, such as low physical activity and high consumption of sugary foods and drinks. The majority of respondents also have limited access to health information and routine checkups. The conclusion of this study is that early detection is a fundamental step in identifying at-risk individuals, allowing for immediate intervention in the form of health education and medical referral. This research is expected to serve as a foundation for more structured and sustainable public health programs in the region.